Picture Guessing Game -Based Learning Module as a means Improving Elementary School Physical Education Learning Outcomes - Yudesta Efaliana; Kuswanto, Cahniyo Wijaya; Putri Zakia; Oktaria Kusumawati (UNIB Press, 2024)
This research is based on problems found by researchers, namely the unavailability of teaching materials that are in accordance with the curriculum used and the existing teaching materials do not fully meet the needs of students. This research aims to develop a physical education, sports and health (PJOK) learning module based on a picture guessing game. This research and development uses a model from Robert Maribe Branch. The data collection instrument used a questionnaire given to three experts, namely media experts who scored 76% in the